Differentially expressed genes, lncRNAs, and competing endogenous RNAs in Kawasaki disease - Guo, Changsheng; Hua, Yuanqing; Qian, Zuanhao (PeerJ, 2021)
Background Kawasaki disease (KD) is an acute and febrile systemic vasculitis of unknown etiology. This study aimed to identify the competing endogenous RNA (ceRNA) networks of lncRNAs, miRNAs, and genes in KD and explore the molecular mechanisms underlying KD. Methods GSE68004 and GSE73464 datasets were downloaded from the Gene Expression Omnibus. Differentially expressed lncRNAs (DElncRNAs) and genes (DEGs) in KD were identified using the criteria of p < 0.05 and | log2 (fold change) | ≥ 1. MicroRNAs (miRNAs) related to KD were searched from databases. The lncRNA-miRNA-mRNA networks involving the DElncRNAs and DEGs were constructed. Results A total of 769 common upregulated, 406 common downregulated DEGs, and six DElncRNAs were identified in the KD samples. The lncRNA-miRNA-mRNA network consisted of four miRNAs, three lncRNAs (including the upregulated PSORS1C3, LINC00999, and the downregulated SNHG5) and four DEGs (including the downregulated GATA3 and the upregulated SOD2, MAPK14, and PPARG). Validation in the GSE18606 dataset showed that intravenous immunoglobulin treatment significantly alleviated the deregulated profiles of the above RNAs in KD patients. Three ceRNA networks of LINC00999-hsa-miR-6780-SOD2, PSORS1C3-hsa-miR-216a-PPARG/MAPK14, and SNHG5-hsa-miR-132/hsa-miR-92-GATA3 were identified. Four genes were associated with functional categories, such as inflammatory response and vascular endothelial cell. Conclusions The ceRNA networks involve genes, such as SOD2, MAPK14, and PPARG, and lncRNAs, including PSORS1C3, LINC00999, and SNHG5, which might play a key role in the pathogenesis and development of KD by regulating inflammation.
Keywords: Kawasaki disease; Microarray; Competing endogenous RNA; Long non-coding RNA